Strawson, Responsibility, and Fittingness - E. V. Loginov (Омский научный вестник: Серия "Общество. История. Современность")
In this article I am developing Peter Strawsonʼs theory of moral responsibility. I am trying to show that it can be freed from sentimentalism and at the same time preserve what makes it attractive for metaphysical discussions about free will. The basis of my strategy is to rethink the concept of fittingness and give reasons the status that emotions have in Strawson’s view.